pls tell the answer fast guys
Attachments:
![](https://hi-static.z-dn.net/files/dfd/d0df2b34408fbd142cdf491f96f64c7d.jpg)
Answers
Answered by
1
Answer:
Properties used,
a^x ÷ a^y = a^(x-y)
(a/b)^-n = (b/a)ⁿ
Step-by-step explanation:
(-3/4)^-5 ÷ (-3/4)^-3 = (-3/4)^[-5-(-3)] = (-3/4)^(-5+3)
= (-3/4)^-2 = (-4/3)² = 16/9
Answered by
1
Step-by-step explanation:
This is correct answer.
Please mark as brainliest answer.
Attachments:
![](https://hi-static.z-dn.net/files/d9f/01e94dda603cbf5e819defdad437a555.jpg)
Similar questions